Aspectos comparativos de los hogares con y sin jóvenes en México: una primera aproximación a partir de la información del II Conteo de Población y Vivienda - Román Reyes, Patricia; Padrón Innamorato, Mauricio (El Colegio de México A.C., 2009)
This paper analyzes some of the comparative features of Mexican households with and without youths, based on the 2nd Population and Housing Survey. It seeks to contribute to the diagnoses of the youth situation in Mexico to enrich the discussion of the impact that household features have on living conditions, insertion into the job and education market of the population ages 12 to 29.